Hepatocellular carcinoma – clinicopathological characteristics, survival, and expression of various histologic molecular markers - Nikolova, Dafina; Ivanova, Viktorija; Dimitrova, Magdalena; Jovanovik, Rubens; Kunovska, Slavica; Orovcanec, Nikola; Petrushevska, Gordana; Janevska, Vesna (Polish Journal of Pathology, 2019)
The aim of this study was to make a clinical characterisation of patients with hepatocellular carcinoma and to investigate the expression of a set of molecular markers in patients from the Republic of North Macedonia. We analysed 60 patients for clinicopathologic factors, and we investigated tumour tissue and surrounding liver tissue for immunoexpression of E-cadherin, β-catenin, cyclin D1, and p53. Infection with hepatitis virus B and C (p < 0.001), tumour dimension (p < 0.001), vascular invasion (p < 0.002), and tumour differentiation (p < 0.021) significantly influenced the survival of the patients. E-cadherin and β-catenin expression reduction and cyclin D1 and p53 overexpression were significantly higher in the tumour than in the non-tumour tissue (p < 0.001; p < 0.001; p = 0.001; p < 0.001, respectively). No significant correlation was found between clinicopathological characteristics and the analysed molecules nor between the molecules themselves. The immunoexpression of E-cadherin, β-catenin, cyclin D1, and p53 was not related to the tumour aggressiveness and prognosis. However, their significantly higher expression in HCC tissue compared to that in non-tumour tissue indicate their important role in hepatocarcinogenesis. The clinicopathological characteristics of the neoplasm remain highly predictive factors for the survival of the patients.